Efecto de la deuda externa sobre el déficit fiscal: caso Latinoamérica, período 2000 – 2020 - Ordóñez Hernández, María Isabel (2023)
Given the impact of the fiscal deficit on macroeconomic stability, this has been slightly reduced, since the region has had a reduction of 5.4% of GDP in 2020 and in 2021 it has only been reduced by 1%. This has had a joint change with the constant increase in external debt, since the Latin American region has had an increase in debt of 22.4% of GDP and in 2020 it would increase exponentially by 40.8% of GDP. This is why the present study aims to determine the effect that debt and other variables can have on this. Data from 18 Latin American countries between 2000 and 2020 were used to analyze the evolution of the main variables, and to generate a GLS model to determine correlation and a GMM to determine the effects of debt and other control variables on the deficit. It was found that the main variables have a permanent 3 presence in Latin America, and that debt has a positive relationship with the fiscal deficit, given that an increase of 1 percentage point of debt increases the deficit by up to 1.85 percentage points. It was also shown that economic growth and natural resource revenues reduce the deficit. Based on this, the study proposes crosscutting policy measures such as innovation policies, trade policies, and policies to encourage financing that promote a change in the productive matrix and investment incentives. An effective VAT reduction is also proposed to reduce the fiscal deficit and minimize the negative effects of reducing it.